"Regioselective Deposition" Method to Pattern Silver Electrodes Facilely and Efficiently with High Resolution: Towards All‐Solution‐Processed, High‐Performance, Bottom‐Contacted, Flexible, Polymer‐Based Electronics. (20th February 2014) - Ji, Deyang; Jiang, Lang; Guo, Yunlong; Dong, Huanli; Wang, Jianpu; Chen, Huajie; Meng, Qing; Fu, Xiaolong; Tian, Guofeng; Wu, Dezhen; Yu, Gui; Liu, Yunqi; et al.
<x xml:space="preserve">Abstract</x> "Regioselectivity deposition" method is developed to pattern silver electrodes facilely and efficiently by solution‐process with high resolution (down to 2 μm) on different substrates in A4 paper size. With the help of this method, large‐area, flexible, high‐performance polymer field‐effect transistors based on the silver electrodes and polyimide insulator are fabricated with bottom‐contact configuration by all‐solution processes. The polymer devices exhibit high performance with average field‐effect mobility over 1.0 cm2 V−1 s−1 (the highest mobility up to 1.5 cm2 V−1 s−1) and excellent environmental stability and flexibility, indicating the cost effectiveness of this method for practical applications in organic electronics.